Epigenetic regulation of axon and dendrite growth - Trakhtenberg, Ephraim F.; Goldberg, Jeffrey L. (Frontiers in Molecular Neuroscience, 2012)
Neuroregenerative therapies for central nervous system (CNS) injury, neurodegenerative disease, or stroke require axons of damaged neurons to grow and reinnervate their targets. However, mature mammalian CNS neurons do not regenerate their axons, limiting recovery in these diseases (Yiu and He, 2006). CNS’ regenerative failure may be attributable to the development of an inhibitory CNS environment by glial-associated inhibitory molecules (Yiu and He, 2006), and by various cell-autonomous factors (Sun and He, 2010). Intrinsic axon growth ability also declines developmentally (Li et al., 1995; Goldberg et al., 2002; Bouslama-Oueghlani et al., 2003; Blackmore and Letourneau, 2006) and is dependent on transcription (Moore et al., 2009). Although neurons’ intrinsic capacity for axon growth may depend in part on the panoply of expressed transcription factors (Moore and Goldberg, 2011), epigenetic factors such as the accessibility of DNA and organization of chromatin are required for downstream genes to be transcribed. Thus a potential approach to overcoming regenerative failure focuses on the epigenetic mechanisms regulating regenerative gene expression in the CNS. Here we review molecular mechanisms regulating the epigenetic state of DNA through chromatin modifications, their implications for regulating axon and dendrite growth, and important new directions for this field of study.